Implementasi Kepemimpinan Kepala Desa Dalam Pembangunan Di Pedesaan Melalui Pendekatan Transformasional - Afandi, Muhamad Nur (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2012)
Role in the development community is very important in supporting development to foster public awareness in the development process. Changes in community development can occur on public awareness itself it will unconsciously create public awareness for the better. In the context of the village leadership, leadership is defined as an art and science that make up a person to influence and direct way of thinking, behaving and acting that lead people and organizations aimed at achieving the vision. Transformational leadership in the development needed to support better development that aims to improve motivation and performance in the implementation of rural development. Head of the village into an important role in making changes in their area. Development in the countryside will be more easy to administer when a village community can understand the characteristics and needs in the development process through the concept of a transformational approach. The results showed transformational leadership in the district mayor of Bandung regency Cimenyan uniformly to all components. Idealism influence, inspirational motivation, individualized consideration, intellectual stimulation and 25% respectively. This means that the behavior of the leader gives a value of 100%. However, its influence will be felt by society as an impetus to address the differences (interests, opinions, ideas, potential, competence, and insight) in a wise and find a solution that is acceptable to society as much as possible. This fact shows the village chief in the District of Bandung Regency Cimenyan transformational approach to leadership in raising public awareness to participate in development.